2024
DOI: 10.14228/jpr.v1i2.45
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Facial Trauma Severity in Cipto Mangunkusumo Hospital Using FISS Scoring System

Abstract: Many scoring systems were introduced to search prognostic value in trauma patients. Facial trauma is a special trauma because it can cause many disabilities in facial function. There have been several reports on facial severity scoring system, such as Facial Injury Severity Score (FISS) and Maxillofacial Injury Severity Score (MFISS). Although these scoring systems have been introduced in many journals, they are not yet used by many clinicians because of their unawareness of its beneficiary. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It might be due to the exclusion criteria in this study, which excluding multitrauma patients that certainly require a longer hospitalization period. However, the results of this research are in line with the previous studies conducted in Manado and Jakarta [9], [10].…”
Section: Discussionsupporting
confidence: 92%
“…It might be due to the exclusion criteria in this study, which excluding multitrauma patients that certainly require a longer hospitalization period. However, the results of this research are in line with the previous studies conducted in Manado and Jakarta [9], [10].…”
Section: Discussionsupporting
confidence: 92%
“…Originally FISS was described as anatomically-based by the methodology of calculation in many of previously published studies 1,2,7,[10][11][12] , but considering specific categorization of such grading trauma system, we could resume that this criteria is also partially functionally-oriented, even if such traumatic functional association is not so directly represented, as in MFISS methodology. For example, Le Fort III fracture gains greater score than Le Fort I or Le Fort II, which is logical, because such fracture is causing greater anatomical disruption, but it should be noted that Le Fort III fracture is also associated with more pronounced functional alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the number of previously published studies it is argumentative to resume that maxillofacial injury severity scoring system (MFISS) and facial injury severity scoring system (FISS) are considered as ones of the most prevalent among researchers' use 1,6,7,[9][10][11][12] , while in one of the studies such conclusion even was solidly clarified 2 . Taking into account original scoring methodologies of MFISS and FISS scores and available literature data on their use with research objective, the first one is considered to be more functionally-oriented, while second -anatomically-based 1,2,6,7,[9][10][11] . On the other hand number of publications revealed that both of these scores demonstrated comparatively analogical statistical associations with treatment duration, rehabilitation charges, injury severity, complication rates and some other parameters 1,2,7,[10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Bangun in 2009 in Ciptomangunkusumo Hospital found that from FISS scoring system, they found that most of maxillofacial trauma in Cipto Mangunkusumo hospital in 2009 was mild trauma. This is probably due to the mechanism of trauma which was low velocity injury of motorcyclist (Bangun et al 2012). A study from Ramalingam found that based on the results of his study, maxillofacial injury severity measured by MFISS and FISS scores are predictable indicators of the economic burden to the patients (Ramalingam 2015).…”
Section: Discussionmentioning
confidence: 99%